If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + -9) = 13 + -1x Reorder the terms: 3(-9 + x) = 13 + -1x (-9 * 3 + x * 3) = 13 + -1x (-27 + 3x) = 13 + -1x Solving -27 + 3x = 13 + -1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'x' to each side of the equation. -27 + 3x + x = 13 + -1x + x Combine like terms: 3x + x = 4x -27 + 4x = 13 + -1x + x Combine like terms: -1x + x = 0 -27 + 4x = 13 + 0 -27 + 4x = 13 Add '27' to each side of the equation. -27 + 27 + 4x = 13 + 27 Combine like terms: -27 + 27 = 0 0 + 4x = 13 + 27 4x = 13 + 27 Combine like terms: 13 + 27 = 40 4x = 40 Divide each side by '4'. x = 10 Simplifying x = 10
| 112-4x=23x+16 | | -4m+2(6m+1)=23+m | | -108+x=-5x+42 | | 5x+x+(4x-16)=180 | | 2x+6=1.75x+6 | | 2x+6=12-7x | | x^2-8=7x | | 78-4x=2x+12 | | 5b+11-4b=56 | | -9p-5=93 | | e^2x=57 | | 6(5a-1)(3a+1)=0 | | 3t/5-6=t/12 | | 4(x-3)=x+3 | | (7+w)(2w+9)=0 | | 10b+9-3b=4 | | 10-8x=36-15x | | x-67=-10x+131 | | 10+2(x+2)=20 | | -7(n+7)=-9-2n | | s^2-3s=0 | | 9x^4-144x^2= | | x^2-90-3=0 | | 163-6x=6x+7 | | 3t(7t+4)= | | 2(3x+2)=5(x+2) | | -2x^3+19x^2y-15x^2y+11x^3= | | 15=-7+r | | -X/3=11 | | 18+y=12 | | 6+m=18 | | x/3=-7 |